(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
The digital economy era demands micro-enterprises to possess adaptive innovation and competitiveness in order to survive and grow. Entrepreneurial education plays a strategic role in equipping business actors with technical, managerial, and digital literacy competencies relevant to modern market dynamics. This study employs a qualitative approach using a literature review method and descriptive analysis. Secondary data were obtained from 50 scholarly articles accessed through Google Scholar and other credible academic websites, covering publications from 1964 to 2025. After a rigorous selection process based on relevance and methodological validity, 31 articles were used as primary sources. The data analysis technique involved three stages: grouping articles according to key variables, identifying patterns and inter-variable relationships, and synthesizing findings to derive conceptual conclusions. The results indicate that entrepreneurial education significantly enhances innovation, operational efficiency, and micro-enterprise competitiveness, thereby contributing positively to community welfare in the digital economy era